Connection of anthropometric indicators and motor abilities of primary school students - Vukićević Veljko; Lukić Nikola; Zečević Stanko (College of Sports and Health, Belgrade, 2020)
The aim of the study was to determine the association between manifest variables of motor skills and body mass index in elementary school students aged 9 to 12. The study was of a transversal nature, that is, only one measurement was conducted on this population of students. The sample consisted of third, fourth, fifth and sixth grade male students from the elementary school "Svetozar Miletic" in Vrbas, a total of 95 respondents. In order to determine the coreelation between predictor variables system and the criterion variable, as well as the individual contribution of the predictor to the definition of the criterion variables, linear regression analysis was applied. The obtained results show that there is a statistically significant correlation in the 3rd grade students in the variables of deep trunk inclination and high hinge with the body mass index, there is no statistically significant correlation of manifested motor skills variables with the body mass index in the 4th and 5th grade students. The 6th grade students show statistically significant correlation between the trunk flexion variables for 30 s and block start 30m sprint with body mass index. Attitudes towards the teacher provide valuable information about what students think and feel about them, thus creating adequate conditions for effecting change and improving both teaching and relationships with students.